Classification, natural history and staging of idiopathic pulmonary fibrosis - Poletti, V.; Egan, J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is defined as a fibrosing disease limited to the lungs of unknown aetiology characterised radiologically and/or morphologically by the usual interstitial pneumonitis pattern. It is a disease with an ominous prognosis. There is currently no consensus regarding the staging and classification of IPF. As highlighted in the revised ATS/ERS guidelines, proposed stages may be based on resting pulmonary function test measurements and/or the extent of radiologic abnormalities, but it is unknown if these staging approaches are relevant to clinical decision-making. Thus, the unmet needs in IPF include a complete knowledge of the pathogenetic mechanisms leading to lung destruction, an improved understanding of different clinico-radiological subtypes of this disorder and finally, the identification of staging systems of clinical value.